Social theory : a historical introduction - Callinicos, Alex, 1950- (Oxford : Polity, 1999)
The enlightenment. Hegel. Liberals and reactionaries. Marx. Life and power. Durkheim. Weber. The illusions of progress...
Keywords: Philosophy; Social sciences; Social sciences -- Philosophy; Social sciences -- Philosophy -- History